2015
DOI: 10.1021/jz5025542
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of N2 Dissociation upon Inner-Valence Ionization by Wavelength-Selected XUV Pulses

Abstract: Ionization of nitrogen by extreme ultraviolet (XUV) light from the Sun has recently been recognized as an important driver of chemical reactions in the atmosphere of Titan. XUV photons with energies of 24 eV and above convert inert nitrogen molecules into reactive neutral and ionic fragments that initiate chemical reactions. Understanding the XUV-induced fragmentation poses significant challenges to modern theory owing to its ultrafast time scales, complex electronic rearrangements, and strong dependence on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 28 publications
(59 reference statements)
5
63
0
Order By: Relevance
“…2(a)], the theoretical kinetic energy spectrum exhibits a very intense band between 0 and 1.5 eV and a much weaker band between 2 and 4 eV. The intensity of the latter band is significantly underestimated by theory, since this band results mainly from population of highly excited states of N 2 þ [19] and of dissociative channels of N 2 2þ not included in the present calculations. As can be observed in this figure, there are only two groups of states that significantly contribute to the lower band, namely, those leading to Nð 2 DÞ þ N þ ð 3 PÞ and Nð 2 PÞ þ N þ ð 3 PÞ, while practically all dissociative ionization channels included in our calculations contribute to the upper band.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…2(a)], the theoretical kinetic energy spectrum exhibits a very intense band between 0 and 1.5 eV and a much weaker band between 2 and 4 eV. The intensity of the latter band is significantly underestimated by theory, since this band results mainly from population of highly excited states of N 2 þ [19] and of dissociative channels of N 2 2þ not included in the present calculations. As can be observed in this figure, there are only two groups of states that significantly contribute to the lower band, namely, those leading to Nð 2 DÞ þ N þ ð 3 PÞ and Nð 2 PÞ þ N þ ð 3 PÞ, while practically all dissociative ionization channels included in our calculations contribute to the upper band.…”
Section: Resultsmentioning
confidence: 74%
“…A similar approach exploiting narrow band XUV radiation has been used to investigate autoionization in O 2 [17], as well as the creation of highly excited states in N 2 [18]. Dissociative ionization of N 2 was further studied in a recent work applying femtosecond time-resolved photoelectron and photoion spectroscopy using a tabletop XUV time-compensating monochromator [19]. The major drawback of using attosecond pulse trains is the reduced temporal resolution associated with recursive excitation events.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed how femtosecond VUV and XUV radiation can be used to reveal transient nuclear and electron dynamics in diatomic molecules [8][9][10][11][12] as well as in more complex molecular systems [13,14]. To probe such dynamics, the majority of the pump-probe-style experiments accomplished to date utilize not only pairs of XUV-IR pulses [8,[15][16][17][18], but also a combination of VUV-XUV pulses [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…We attribute the strongest feature (shaded blue) to low kinetic energy N + 2 ions and predissociation of the N + 2 C 2 Σ + u state [51]. The contribution shaded in green has previously been assigned to dissociation from the F 2 Σ + g state, and the features in the area shaded in orange are associated with dissociation from the highly-excited Rydberg-like states of N + 2 and the H band [51][52][53]. Figure 6c,f shows the photoelectron momentum distribution and the photoelectron kinetic energy spectrum, respectively.…”
Section: Data Acquisitionmentioning
confidence: 95%
“…The much weaker contributions of the other cationic and dicationic states are not shown for clarity [53,54,56,57]. The signal at kinetic energies smaller than 1 eV can be assigned to highly excited inner valence states of N + 2 and possibly the first electronic states of N 2+ 2 [52,53,57]. As mentioned earlier, in order to extract information about the correlation between the different single-shot datasets, it is important that the sets are acquired simultaneously and can be analyzed in a synchronized fashion.…”
Section: Data Acquisitionmentioning
confidence: 99%